A arbitragem de litígios envolvendo entes públicos como tendência do processo civil contemporâneo - Fernandes, Jeane Santos Bernardino (2011)
This essay opens up about the unpretentious attempt to tack marks doctrine and jurisprudence on the use of arbitration in domestic and international commercial contracts, aiming to operate a critical analysis of the weights that advocate the barriers to adoption of private methods of conflict resolution arising under state contract. Dissent befallen the spontaneous fulfillment of government contracts, it is imperative to help the resolution of the dispute mechanisms. Considering the crisis of credibility of the judiciary, delays in proceedings, and often, lack of understanding of the specificities and peculiarities of contracting this work dissertational promotes the defense of arbitration to the demarcation dispute had in the achievement of such contracts. It should proceed to investigate the views, trends and prospects of resolving conflicts in property contracts signed by state and parastatal entities nationally and internationally, giving rise to an analysis of vestibular problems extracted from there. The key point to be faced erects itself on the strength of traditional doctrine accepting the arbitration of domestic and international commercial arbitration for the intended scope, the ground affront to constitutional principles and attachments normative legal ruling. Aiming debug prints retrograde and unthinking assertions, it should be brought to light perception renewals and compliance internationalist issue for the debate on the national scene will conform to the current situation. The work goes through, respectively: a) the baseline concept of arbitration and the institutes of public procurement in its arrangements, b) analysis of the shortcomings of the judiciary as one of the reasons for the adoption of arbitration and the impact of new limits on the elimination of dissent in public procurement through non-judicial, treat, yet c) the failure plexus rules at national level as a cause enough to opt for alternatives to the current state interference in order to conclude by the powerless of arbitration; d) harmonization of laws you want, without necessary changes in the embargo regulations elementary developed so far. This thirst lauds the study of brief notes about some of the hotspots of choice for domestic arbitration and international commercial contracts in public, stressing the dissonance of doctrine and jurisprudence on the subject in focus.